TAX AVOIDANCE IN PROFITABILITY, LEVERAGE, AND SALES GROWTH - Sari, Diana; Andriana, Nadila; Fadjar, Achmad (International Journal of Psychosocial Rehabilitation, 2020)
This study aims to find out whether profitability, leverage and sales growth affect tax avoidance. The factors tested in this study are profitability, leverage, and sales growth as an independent variable, and tax avoidance as the dependent variable. The research method used was explanatory research. The type of research data in the form of secondary data is the financial statements of manufacturing companies listed on the Indonesia Stock Exchange during 2015-2017. The population in this study were 30 manufacturing companies listed on the Indonesia Stock Exchange during 2015-2017, with a sample determination technique using purposive sampling technique to obtain as many as 90 annual financial statements of manufacturing companies listed on the Indonesia Stock Exchange during 2015-2017. The results of hypothesis testing partially indicate that protection affects tax avoidance, leverage affects tax avoidance, and sales growth affects tax avoidance. The results of simultaneous hypothesis testing show profitability, leverage, and sales growth together influencing tax avoidance. The contribution of profitability, leverage, and sales growth is influenced by tax avoidance of 12.15%, while the remaining 87.85% is explained by other variables outside the research model.